Challenges and opportunities in video coding for 3D TV - Kalva, Hari; Mayron, Liam M.; Christodoulou, Lakis (My University, 2006)
This paper explores the challenges opportunities in developing and deploying 3D TV services. The 3D TV services can be seen as a general case of the multi-view video that has been receiving significant attention lately. The keys to a successful 3D TV experience are the availability of content, the ease of use, the quality of experience, and the cost of deployment. Recent technological advances have made possible experimental systems that can be used to evaluate the 3D TV services. We have developed a 3D TV prototype and have currently conducting our first user study to evaluate the quality and experience. These experiences have allowed us to identify challenges and opportunities in developing 3D TV services
Keywords: Communication, Networking & Broadcasting; 3-D television; Three-dimensional display systems; Motion pictures; Multimedia systems